2022
DOI: 10.3389/fimmu.2022.834851
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sex Hormone Levels and Clinical Outcomes in Patients With COVID-19 Admitted to Hospital: An Observational, Retrospective, Cohort Study

Abstract: Understanding the cause of sex disparities in COVID-19 outcomes is a major challenge. We investigate sex hormone levels and their association with outcomes in COVID-19 patients, stratified by sex and age. This observational, retrospective, cohort study included 138 patients aged 18 years or older with COVID-19, hospitalized in Italy between February 1 and May 30, 2020. The association between sex hormones (testosterone, estradiol, progesterone, dehydroepiandrosterone) and outcomes (ARDS, severe COVID-19, in-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Currently, there are data, divided by sex, on the incidence of long-COVID-19 only in the adult population. Quite interestingly, long-COVID-19 appears to be more probable in women than in men [46] in contrast to severe acute COVID-19 [47,48], independent of the severity of the original infection. Other risk factors for having long-COVID-19 seem to be a higher body mass index and older age [49][50][51].…”
Section: Discussionmentioning
confidence: 93%
“…Currently, there are data, divided by sex, on the incidence of long-COVID-19 only in the adult population. Quite interestingly, long-COVID-19 appears to be more probable in women than in men [46] in contrast to severe acute COVID-19 [47,48], independent of the severity of the original infection. Other risk factors for having long-COVID-19 seem to be a higher body mass index and older age [49][50][51].…”
Section: Discussionmentioning
confidence: 93%
“…Knowledge of sex differences is an essential ingredient in developing precision medicine ( 7 ). It has been found that sex could affect the manifestation and pathophysiology of many diseases ( 9 11 ). The impact of sex on outcomes in patients with sepsis has been widely investigated, yielding conflicting results ( 35 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective study of 261,255 critically ill patients revealed that women less than 50 years of age had lower adjusted mortality than men ( 8 ). Moreover, different disease processes and outcomes between men and women were also found in some specific disease groups, like coronary artery disease ( 9 ), acute ischemic stroke ( 10 ) and coronavirus disease 2019 ( 11 ). This may be associated with the influence of sex hormones on the modulation of inflammation during immune responses ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, low testosterone levels that can be seen in older men have been associated with immunological changes that can lead to an increased likelihood of infection [ 9 ]. More specifically, low testosterone has been associated with a higher likelihood of severe COVID-19 pneumonia [ 18 , 19 , 20 , 21 ]. Additionally, mucociliary clearance in the respiratory tract is reduced in older individuals, as has been shown in a study among healthy volunteers of different ages in whom mucociliary clearance and ciliary beat frequency were calculated and were found to be lower in older individuals [ 5 ].…”
Section: Discussionmentioning
confidence: 99%